Optimal Heterogeneous Distributed Storage Regenerating Code at Minimum Remote‐Repair Bandwidth Regenerating Point. Issue 3 (1st June 2016) - Xu, Jian; Cao, Yewen; Wang, Deqiang; Wu, Changlei; Yang, Guang
Abstract : Recently, a product‐matrix (PM) framework was proposed to construct optimal regenerating codes for homogeneous distributed storage systems (DSSs). In this paper, we propose an extended PM (EPM) framework for coding of heterogeneous DSSs having different repair bandwidths but identical storage capacities. Based on the EPM framework, an explicit construction of minimum remote‐repair bandwidth regenerating (MRBR) codes is presented for a specific heterogeneous DSS, where two geographically different datacenters with associated storage nodes are deployed. The data reconstruction and regeneration properties of the MRBR code are proved strictly. For the purpose of demonstration, an example implementation of MRBR code is provided. The presented MRBR code is the first optimal strict‐regenerating code for heterogeneous DSSs. In addition, our proposed EPM framework can be applied to homogeneous systems also.